PROTECTION OF THE AIR OF THE FOUNDRY ENTERPRISES AGAINST POLLUTION OF HARMFUL ORGANIC MATTERS - Yu. P. Shapovalov; A. S. Galibus; A. I. Sudarev; E. M. Glushen; R. K. Nagorny (Литьë и металлургия)
nformation on a problem of pollution of ventilating air of foundry shops and experience of the solution of this problem is provided.